The Identification of Green Banking Concept and Bank Liability (A Study of Act Number 10 of 1998 with Extensive Interpretation and Progressive Legal Approach) (Journal of Private and Commercial Law, 2018)
The purposes of this research are to analyze the identification of Green Banking concept in the Act Number 10 of 1998 with extensive interpretation and progressive legal approach and to analyze how banks should be held liable for based on applicable law in view of the extensive interpretation and progressive legal approach. This research is a normative legal research that has analyzed Green Banking concept using Act Number 10 of 1998 concerning Banking, Bank Indonesia Regulation Number 14/15/PBI/2012 concerning Asset Quality of Commercial Banks, Act Number 32 of 2009 concerning Environmental Protection and Management and the Financial Services Authority Regulation Number 51/POJK.03/2017 concerning the Application of Sustainable Finance for Financial Services Institutions, Issuer Companies and Public Companies, and then presented as prescriptive research. The result of this study is that banks are reluctant to further examine the AMDAL of financed projects and do not oversee such projects until the termination of the contract. Extensive interpretation and progressive legal approach can be used to provide bank a deep insight regarding the concept of green banking contained in the banking law and the extent to which banks (creditors) are subject to the terms of the lender liability.